Tantangan dan Potensi Peradilan Adat sebagai Access to Justice melalui Pengakuan Hukum Adat dalam UUD 1945 - Aurelia, Jessica; Rudijanto, Maria Natasha; Putri, Audrey Bilbina; Felicia, Gladys; Peters, Raphaellee; Neltje, Jeane (Peneliti.net, 2024)
This research examines the challenges and potential of customary courts as an access to justice for indigenous peoples through public services related to the recognition of the existence of customary law in the 1945 Constitution. Customary justice is a traditional legal system that still plays an important role in the lives of indigenous peoples in Indonesia. However, customary justice faces a number of challenges in integrating itself with the national legal framework, especially in the context of the recognition of customary law in the 1945 Constitution. This research will identify the obstacles faced by customary courts in providing access to justice for indigenous peoples, and analyze the potentials that can be utilized to enhance the role of customary courts as effective and inclusive justice institutions. The results of this research can provide useful insights in developing policies and strategies to strengthen customary courts as an integral part of the Indonesian legal system.